The Effect of Secretome MSCs on the expression of MCP-1 and PDGF in Subtotal Nephrectomy Animal Model - Mohammad Ariq Nazar; Nurul Hidayah; Dian Respati Ayu; Nadya Audina Nurkhafiya Sadikin; Naufal Sebastian Anggoro (Indonesian Journal of Medical and Pharmaceutical Science, 2026)
Background: Secretome MSCs [TDPR1.1]have ability to modulation of inflammation, induce angiogenesis, and inhibition of apoptosis of renal cells. Objective: To investigate the role of secretome MSCs administration on the expression of MCP-1 and PDGF in STN animal model. Methods: Subtotal nephrectomy performed in the flank region for unilateral nephrectomy on the right kidney, followed by ablation of superior and inferior poles of the left kidney. The subject rats were equally divided into three groups, six rats each group, namely: Sham operation (SO), Control (CO) and Secretome MSCs (SM). After 14 days of SN induction, established CKD was injected with 250 µL secretome MSCs in the intravenous tail, with the administration repeated every 4 days. The CO received 250 µL saline. The animal sacrifice was carried out 4 days after the last secretome MSCs administration. Results: Relative expression of mRNA MCP-1 of the kidney SN rats showed a significant decrease (P<0.05) and Relative expression of mRNA PDGF of the kidney SN rats showed a significant decrease (P<0.05). Conclusion: In this study, we demonstrate that administration of secretome MSCs was able to reduce MCP-1 and PDGF gene expression, which may contribute to mitigating inflammation in a subtotal nephrectomy-induced CKD animal model.